Influence of the finite Q-factor on excitation of wakefield oscillations in dielectric cavity by a sequence of relativistic electron bunches in the presence of detuning between the resonant frequency and the bunch repetition frequency - Balakirev, V.A.; Onishchenko, I.N.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2015)
Excitation of Cerenkov wakefield oscillations in dielectric cavity with finite value of Q-factor in the presence of detuning between the bunch repetition frequency and the resonant frequency of the excited oscillations is investigated. It is shown that the picture of wake oscillations excitation is determined by the ratio between the value of the Q-factor and frequency detuning parameter πω/δω. For the high Q-factor dielectric cavity Q >>πω/δω picture of wake oscillations excitation is the same as in the cavity without ohmic losses. If the opposite condition is satisfied, the process of wakefield excitation occurs almost as well as in the case of resonant excitation. Linear growth of the wakefield amplitude at initial stage reaches its saturation level.